Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 211886 by Spillover last updated on 23/Sep/24

Answered by Ghisom last updated on 23/Sep/24

∫(√(cos^2  x +cos x)) dx=∫(√(2cos x)) cos (x/2) dx=       [t=(((√2)sin (x/2))/( (√(cos x)))) ⇔ x=2arctan (t/( (√(t^2 +2)))) → dx=((√(2cos^3  x))/(cos (x/2)))dt]  =2∫(dt/((t^2 +1)^2 ))=(t/(t^2 +1))+arctan t =  =(√(2cos x)) sin (x/2) +arctan (((√2) sin (x/2))/( (√(cos x)))) +C

cos2x+cosxdx=2cosxcosx2dx=[t=2sinx2cosxx=2arctantt2+2dx=2cos3xcosx2dt]=2dt(t2+1)2=tt2+1+arctant==2cosxsinx2+arctan2sinx2cosx+C

Answered by Spillover last updated on 23/Sep/24

(√(cos^2 x+cos x)) dx  Let     cos x=sin^2 t      dx=((−2sin tcos t)/(sin x))dt=−((2sin tcos t)/( (√(1−cos^2 t))))dt  ((2sin tcos t)/( (√(1−cos^2 t))))=−((2sin tcos t)/( (√(1−sin^4 t))))dt=−((2sin tcos t)/( (√((1−sin^2 t)(1+psin^2 t)))))dt  dx=−((2sin tcos t)/( (√((1−sin^2 t)(1+sin^2 t)))))dt  ∫(√(cos^2 x+cos x)) dx  =∫(√(sin^4 t+sin^2 t)) dx  =∫((√(sin^4 t+sin^2 t)) ×−((2sin tcos t)/( (√((1−sin^2 t)(1+sin^2 t)))))dt)  −2∫sin^2 tdt=−2(((−sin tcos t+t)/2))  sin tcos t−t  (√(cos x(1−cos x))) −sin^(−1) (√(cos x)) +C

cos2x+cosxdxLetcosx=sin2tdx=2sintcostsinxdt=2sintcost1cos2tdt2sintcost1cos2t=2sintcost1sin4tdt=2sintcost(1sin2t)(1+psin2t)dtdx=2sintcost(1sin2t)(1+sin2t)dtcos2x+cosxdx=sin4t+sin2tdx=(sin4t+sin2t×2sintcost(1sin2t)(1+sin2t)dt)2sin2tdt=2(sintcost+t2)sintcosttcosx(1cosx)sin1cosx+C

Terms of Service

Privacy Policy

Contact: info@tinkutara.com